Incidence of Klebsiella pneumoniae producing Metallo Beta-Lactamase (MBL) at RSUP Dr. Wahidin Sudirohusodo Makassar - Muhammad Jen Hamdani; Natsir Djide; Mansyur Arif (Sasambo Journal of Pharmacy, 2022)
Bacterial resistance to antibiotic is one of the factors triggering infection therapy failure. This study was conducted to determine the prevalence of carbapenem-resistance Klebsiella pneumoniae infection and the phenotype of carbapenem-resistant Metallo-Beta-Lactamase (MBL)-producing Klebsiella pneumoniae isolates at RSUP Dr. Wahidin Sudirohusodo Makassar. This study included Klebsiella pneumoniae identification on each infectious patient’s isolates. The sensitivity test of antibiotics, phenotype confirmatory test, and MBL phenotypic test were conducted using agar diffusion Kirby-Bauer, Vitek-2-Compact, and Double Disc Synergy Test (DDST) method, respectively. As the result, the antibiotic sensitivity test using the Vitek-2-Compact method on 50 clinical samples (pus, sputum, blood. tissue, urine, brain fluid, and feces) found that 10 isolates (20%) were resistant to carbapenem.  The phenotypic test using the Double Disc Synergy Test (DDST) method found that carbapenem-resistant isolates caused by the production of Metallo Beta Lactamase (MBL) enzymes were 2 isolates or 20% of the total carbapenem-resistant isolates.